Travellers’ destination choice among university students in China amid COVID-19: extending the theory of planned behaviour - Lei, Wang; Wong, P. P. W. *; Zhang, Qi (Emerald, 2021)
Purpose – Prior tourism literature neglected the negative motivational or attitudinal elements influencing individuals’ travel destination decisions. This study aims to examine the relationships between animosity, ethnocentrism, attitude, subjective norm (SN), perceived behavioural control (PBC), destination overall image (DOI) and destination visit intention (DVI). Design/methodology/approach – A quantitative approach was used using a survey methodology involving 402 student responses. The proposed hypotheses were empirically tested with SPSS and AMOS. Findings – The results demonstrated that animosity and ethnocentrism negatively influenced DOI and DVI. A positive relationship was reported between attitude, DOI and DVI. Additionally, SN and PBC positively influenced DVI. Ethnocentrism, PBC and DOI were also identified with statistically significant differences through gender. Meanwhile, statistically significant differences in attitude, PBC, DOI and DVI were evident between postgraduate students and the counterparts. Originality/value – This study extends the existing knowledge on how animosity and ethnocentrism influenced DOI and DVI in tourism literature and benefitted Western tourism and key stakeholders in tourism